Heterogeneous esterification of oil with high amount of free fatty acids - Marchetti, Jorge Mario (2007)
Frying oils have become the newest raw material for the transesterification reaction for the production of biodiesel. However, these compounds usually come with a certain amount of free fatty acids. These impurities can be transformed into esters and the production of biodiesel could be increased. The use of basic resins to perform the esterification reaction into biodiesel is studied in this work. The effect of the most relevant variables of the process such as reaction temperature, molar ratio between alcohol and oil, amount of catalyst and amount of free fatty acids fed with the oil have been analyzed. For this purpose, an ideal frying oil using oleic acid and soybean oil was made. The alcohol used was ethanol. The esterification of free fatty acid using this heterogeneous catalyst appears as a great alternative to purify frying oil; in this case, the final conversion achieved was around 80%.